Transient metal-centered states mediate isomerization of a photochromic ruthenium-sulfoxide complex - Amy A. Cordones (Nature Portfolio, 2018)
An essential open question in functional transition metal complexes is the relative roles of charge-transfer and metal-centered excited states. Here the authors identify the important role of metal-centered excited states in the linkage photoisomerization of a photochromic Ru-sulfoxide complex.